Revising the taxonomy of corporate accelerators: moving towards an evolutionary perspective. (17th January 2022) - Veit, Philipp; Kramer, Alexander; Kanbach, Dominik; Stubner, Stephan
Corporate accelerators have become integral actors in entrepreneurial ecosystems. They are heterogeneous and rapidly developing entities differing significantly in objectives and design. In this paper, we provide a comprehensive corporate accelerator taxonomy and present its evolution over time. We analyse the population of corporate accelerator programmes active in Germany in late 2019. Building on a unique dataset of 87 semi-structured interviews with managing directors of corporate accelerators, participating startups and corporate documents, we derive distinctive archetypes, differing in strategic objectives and defining characteristics. Based on this contemporary taxonomy, we discuss how corporate accelerators have evolved over recent years and delimit them to similar concepts such as incubators. Thereby, we contribute a holistic understanding of corporate accelerator commonalities and differences and provide the foundation for an evolutionary perspective to the field of corporate accelerator research. For entrepreneurial practice, we add novel insights on the experience-based learnings behind a considerable archetype evolution.